2017
DOI: 10.1128/aem.01503-17
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Dissemination of Antimicrobial Resistance Determinants in Multiple Salmonella Serotypes following Isolation from the Commercial Swine Operation Environment after Manure Application

Abstract: The aim of this study was to characterize the plasmids carrying antimicrobial resistance (AMR) determinants in multiple Salmonella serotypes recovered from the commercial swine farm environment after manure application on land. Manure and soil samples were collected on day 0 before and after manure application on six farms in North Carolina, and sequential soil samples were recollected on days 7, 14, and 21 from the same plots. All environmental samples were processed for Salmonella, and their plasmid contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 76 publications
7
34
0
Order By: Relevance
“…Plasmids were observed specific to Salmonella serovar that was very similar to the AMR genes (Table 3 ). This is in accordance to our previous study that the plasmid profiles were correlated to Salmonella serovar and incompatibility (Inc) groups [ 13 ]. The IncF (both FI and FII) family found across the different Salmonella serovars in our study is known to be a well-adapted and commonly distributed plasmid among members of the Enterobacterceae family [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Plasmids were observed specific to Salmonella serovar that was very similar to the AMR genes (Table 3 ). This is in accordance to our previous study that the plasmid profiles were correlated to Salmonella serovar and incompatibility (Inc) groups [ 13 ]. The IncF (both FI and FII) family found across the different Salmonella serovars in our study is known to be a well-adapted and commonly distributed plasmid among members of the Enterobacterceae family [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…The IncF (both FI and FII) family found across the different Salmonella serovars in our study is known to be a well-adapted and commonly distributed plasmid among members of the Enterobacterceae family [ 53 , 54 ]. Although our data cannot fully explain the transmission of AMR determinants among various species, they are in line with previous studies that reported on the role of animals and environment as important sources of multiple AMR genes as well as plasmids, and that transmission can occur by horizontal gene transfer [ 13 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Eventually, humans could become the ultimate receptors of ARGs. Previous studies have also confirmed that HGT of ARGs could impact food safety by the enrichment of ARGs in the pasture or in the composting process of pig, cow and poultry manure (Soucy et al , 2015; Baker et al , 2016; Pornsukarom and Thakur, 2017).…”
Section: Discussionmentioning
confidence: 82%